THE RELATIONSHIP BETWEEN KNOWLEDGE AND BREAST SELF-EXAMINATION BEHAVIOR (BSE) IN ADOLESCENT FEMALES - Dewi, Riska Agestin Puspita; Wijayanti, Wijayanti; Widyastutik, Desy (Universitas Kusuma Husada Surakarta, 2026)
Background: The incidence of cancer continues to increase, and at this time, breast cancer is in first place in terms of the number of cancers in Indonesia and is one of the contributors to cancer deaths. Breast self-examination (BSE) is one way to detect breast cancer early. This study aims to determine the relationship between knowledge and breast self-examination behavior in adolescent females at SMK Kesehatan Amanah Husada Yogyakarta.Methods: This study used a quantitative, correlational, cross-sectional design. The population of all female students in grades X, XI, and XII of SMK Kesehatan Amanah Husada Yogyakarta for the 2024/2025 school year is 115, and 54 are sampled. Determine the sample for each class using proportionate stratified random sampling and simple random sampling. Data collection was conducted using a questionnaire on breast self-examination knowledge and behavior, which was then analyzed using the chi-square test.Results: Respondents with good knowledge of breast self-examination were 32 (59.3%), enough knowledge as much as 10 (18.5%), and less knowledge as much as 12 (22.2%). In addition, respondents who did not perform breast self-examination behavior were 35 (64.8%), and those who performed were 19 (35.2%). The results of the chi-square test showed a significance value of p < 0.001 instead of p = 0.000.Conclusion: There is a relationship between knowledge and breast self-examination behavior in adolescent females at SMK Kesehatan Amanah Husada Yogyakarta.